Solvatochromic covalent organic frameworks - Emrys Evans (Nature Communications, 2018)
Covalent organic frameworks (COFs) are an emerging class of highly tuneable crystalline, porous materials. Here we report the first COFs that change their electronic structure reversibly depending on the surrounding atmosphere. These COFs can act as solid-state supramolecular solvatochromic sensors that show a strong colour change when exposed to humidity or solvent vapours, dependent on vapour concentration and solvent polarity. The excellent accessibility of the pores in vertically oriented films results in ultrafast response times below 200 ms, outperforming commercially available humidity sensors by more than an order of magnitude. Employing a solvatochromic COF film as a vapour-sensitive light filter, we demonstrate a fast humidity sensor with full reversibility and stability over at least 4000 cycles. Considering their immense chemical diversity and modular design, COFs with fine-tuned solvatochromic properties could broaden the range of possible applications for these materials in sensing and optoelectronics.